Frailty in hypertensive population and its association with all-cause mortality: data from the National Health and Nutrition Examination Survey - Li, Li; Wang, Yuge; Yang, Chunlei; Huang, Chenhui; Duan, Lanzhi; Zhou, Jianghua; Lu, Yanyu; Zhao, Guojun (Frontiers in Cardiovascular Medicine, 2023)
Objectives：This study aimed to investigate the relationship between frailty and all-cause mortality in hypertensive population. Methods：We used data from the National Health and Nutrition Examination Survey (NHANES) 1999-2002, and mortality data from the National Death Index. Frailty was assessed using the revised version of the Fried frailty criteria (weakness, exhaustion, low physical activity, shrinking, and slowness). This study aimed to evaluate the association between frailty and all-cause mortality. Cox proportional hazard models were used to evaluate the association between frailty category and all-cause mortality, adjusted for age, sex, race, education, body mass index (BMI), poverty-income ratio, physical activity, smoking, alcohol, diabetes, arthritis, congestive heart failure, coronary heart disease, stroke, overweight, cancer or malignancy, chronic obstructive pulmonary disease (COPD), chronic kidney disease (CKD), and take medicine for hypertension. Results：We gathered 2117 participants with hypertension; 17.81%, 28.77%, and 53.42% were classified as frail, pre-frail, and robust, respectively. We found that frail [hazard ratio (HR) = 2.76, 95% confidence interval (CI) = 2.33-3.27] and pr-frail (HR = 1.38, 95%CI = 1.19-1.59] were significantly associated with all-cause mortality after controlling for variables. For the age group, we found that frail (HR = 3.02, 95%CI = 2.50-3.65) and pre-frail (HR = 1.35, 95%CI = 1.15-1.58) were associated with all-cause mortality in the age group ≥65. For the frailty components, weakness (HR = 1.77, 95% CI = 1.55-2.03), exhaustion (HR = 2.25, 95%CI = 1.92-2.65), low physical activity (HR = 2.25, 95%CI = 1.95-2.61, shrinking (HR = 1.48, 95%CI = 1.13-1.92, and slowness (HR = 1.44, 95%CI = 1.22-1.69) were associated with all-cause mortality. Conclusion: This study demonstrated that frailty and pre-frailty were associated with an increased risk of all-cause mortality in patients with hypertension. More attention should be paid to frailty in hypertensive patients, and interventions to reduce the burden of frailty may improve outcomes in these patients.